The good mother [videorecording (DVD)] - Joris-Peyrafitte, Miles, 1992-; Harrison, Madison; Swank, Hilary; Cooke, Olivia, 1993-; Dilone, 1994-; Penn, Hopper, 1993-; Lewis, Norm, 1963-; Aldridge, Karen; Reynor, Jack, 1992- (Vertical Entertainment, 2023)
Starring Academy Awardʼ-winner Hilary Swank, the film follows a journalist grieving the murder of her son who forms an unlikely alliance with his pregnant girlfriend to track down the killers in the seedy world of drugs and corruption.